Change in prescription habits after federal rescheduling of hydrocodone combination products - Seago, Susan (Proc (Bayl Univ Med Cent), 2016)
Nationally, health care providers wrote 259 million prescriptions for narcotic analgesics in 2012, or roughly one bottle of narcotics per US adult (1). In an effort to combat this ever-growing problem, the Drug Enforcement Administration changed the schedule of hydrocodone combination products from schedule III to schedule II on October 6, 2014. Fourteen Baylor Scott & White pharmacies encompassing a 200-mile radius in Central Texas were queried for prescription information on hydrocodone/acetaminophen, morphine, codeine/acetaminophen, and tramadol before and after the rescheduling to evaluate trends in prescription drug usage. While the rescheduling of hydrocodone combination products resulted in a reduced number of prescriptions and the total quantity dispensed of both the hydrocodone/acetaminophen 5/325 mg (Norco 5/325) and 10/325 mg (Norco 10/325) formulations, this was offset by a dramatic increase in alternative narcotic analgesics such as tramadol, codeine/acetaminophen 30/300 mg (Tylenol #3), and codeine/acetaminophen 60/300 mg (Tylenol #4), which do not have schedule II requirements. Additionally, there was no significant reduction in total pain medication prescribed after converting all agents to morphine equivalents.